Producto audiovisual para el posicionamiento de los emprendedores agrícolas asociados a la casa de turismo en la ciudad Otavalo, Parroquia San Luis, Provincia Imbabura. - Cabascango, Álvaro D. (2019)
The present investigation is a guide for the elaboration of an advertising audiovisual product in different sectors of enterprises, since it will allow to contribute in the progress and effectiveness of each business. The purpose of this research arises from the need to improve the positioning of agricultural entrepreneurs in the canton of Otavalo, since they have a disadvantage in their growth and business development, having as a challenge to potentiate the agricultural sector of the locality. With the use of research methods it is possible to determine the diagnosis which is an advantage for the recognition of the enterprises waiting for different impacts at the cantonal and national level. By which the knowledge of design and audiovisual qualities collected through the race will be used, implementing solutions to graphic and visual media before the problematic of the traditionalist bad approach towards a demanding public. The present proposal is established in developing an audiovisual product for the positioning of agricultural entrepreneurs allowing the growth of the institution through the advertising audiovisual product.